Households neighboring wildlife protected areas may be at a higher risk of rabies than those located further away: a community-based cross-sectional cohort study at Pian Upe game reserve, Bukedea district, Eastern Uganda - Atuheire, Collins G. K.; Okwee-Acai, James; Taremwa, Martha; Ssajjakambwe, Paul; Munyeme, Musso; Kankya, Clovice; Terence, Odoch; Ssali, Sarah N.; Mwiine, Frank N.; Buhler, Kayla J.; Tryland, Morten (Frontiers in Tropical Diseases, 2024)
Introduction This study examines rabies incidence and associated risk factors at the interface between wildlife and human communities near Pian-Upe game reserve in Eastern Uganda. We hypothesized that human settlements in closer proximity to the reserve would exhibit higher rabies risk compared to those located further away. Methods Using a standard questionnaire, households within <4, 4-14, and >14 km from the Pian Upe game reserve in Bukedea District were interviewed. Data on socio-demographic characteristics, recent rabid animal bites, and suspected human and livestock rabies cases for the past year (2023) were collected after seeking informed consent. Descriptive statistics were used to analyze socio-demographic information and incidence data, while separate binomial generalized linear models with log-link function were used to identify predictors of rabies incidence and mortality. Results Between January and March 2023, 302 participants were interviewed. Respondents had an average age of 44 years with 34% (n=103) being female. All households owned at least one dog, though only 47% (n=142) had vaccinated their dogs against rabies in the past year. Additionally, 39% (n=118) of respondents used dogs for hunting. Rabies annual incidence increased with decreasing distance to the game reserve (7.5 to 15.7% for humans, for the dogs, and 5.0 to 9.8% for livestock, including cows, goats and sheep). Significant factors associated with rabies in humans included primary education level (aRR=3.8, 95%CI 1.0-23.7) and grazing livestock in the reserve (aRR=5.30, 95%CI 1.0-40.3). Mortality was associated with fetching firewood from the game reserve (aRR=4.7, 95%CI 1.3-17.5). Conclusions This study reveals that there is an increased risk of rabies for domesticated animals and people located within proximity to the game reserve. Further efforts to prevent the spread of rabies could include increasing education and awareness for communities along with targeted dog vaccination in settlements surrounding wildlife protected areas.